Women's Rights in Choosing a Partner in Marriage Gender Justice Perspective in Grobogan Regency - Abdul Aziz; Iqbal Subhan Nugraha; Lukman Hakim (MUWAZAH : jurnal kajian gender, 2025)
The choice of a partner in marriage is a fundamental right of women that is often hampered by dominant social and cultural norms, especially in rural areas such as Grobogan Regency, Central Java. Despite increasing awareness of gender justice, women in the area still face various obstacles in expressing their right to choose a life partner. This study aims to explore how women's rights in choosing a partner in marriage are viewed from the perspective of gender justice and its impact on women's empowerment in Grobogan Regency. The method used is qualitative research with a legal social approach through case studies. Data were collected through in-depth interviews with five women; Rabiah, Suliyem, Hartini,Kasmiyati, and Surati in Grobogan and participatory observations. The results show that despite the increased understanding of the right to choose a partner, many women are still affected by social and family pressures in making these decisions. Gender justice in the selection of spouses has been proven to have a positive impact on women's empowerment, both in social, economic, and psychological aspects, by increasing their autonomy and well-being. The implications of this study are the importance of education, advocacy, and local policies that better support women's rights to choose a partner, as well as women's social and economic empowerment at the local level. This research contributes to the understanding of the importance of gender justice in marriage practice, as well as the need for more proactive policy changes in supporting gender equality in society.